2010
DOI: 10.1097/prs.0b013e3181f52710
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical Orthodontics versus No Presurgical Orthodontics: Treatment Outcome of Surgical-Orthodontic Correction for Skeletal Class III Open Bite

Abstract: The results suggest that in surgical-orthodontic correction of skeletal class III open bite, presurgical orthodontics has no clinically significant effects on facial aesthetics, occlusion, or stability. However, presurgical orthodontics has a significant adverse effect on efficiency. Patients receiving presurgical orthodontics undergo longer treatment time than those receiving no presurgical orthodontics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 10 publications
3
127
0
Order By: Relevance
“…Only three studies had performed retrospective cohort analyses to compare the differences between the orthodontics-first and the surgery-first approaches. [27][28][29] The search results indicated that a prospective cohort study or randomized controlled trial on the surgery-first approach has not yet been conducted.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Only three studies had performed retrospective cohort analyses to compare the differences between the orthodontics-first and the surgery-first approaches. [27][28][29] The search results indicated that a prospective cohort study or randomized controlled trial on the surgery-first approach has not yet been conducted.…”
Section: Resultsmentioning
confidence: 96%
“…Studies reported bonding the orthodontic brackets immediately before, [24,25] 1 week before, [19,23,26] 1 month before, [27][28][29] or 1-2 months before [30] surgery. Only one of the papers reported the total elimination of preoperative orthodontic treatment and the fitting of orthodontic brackets 10-14 days after surgery.…”
Section: Treatment Time For Preoperative Orthodontic Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 This approach has some advantages, such as short total treatment duration, early improvement of the facial profile, and establishment of proper maxillomandibular relationship before orthodontic treatment. [2][3][4]7 The SFA can be performed successfully in cases with well-aligned or mildly crowded anterior teeth, mild to moderate curve of Spee/vertical problem, little or no transverse discrepancy, and normal to mildly proclined/retroclined incisor inclination. 2,4 Skeletal improvement through orthognathic surgery can be compromised by inadequate preoperative decompensation of the incisors.…”
Section: Introductionmentioning
confidence: 99%